Hydrogen migration reactions via low internal energy pathways in aminobenzoic acid dications - Vetelainen, Onni; Babayan, Morsal; Pihlava, Lassi; Abid, Abdul Rahman; Kivimäki, Antti; Kukk, Edwin; Walsh, Noelle; Urpelainen, Samuli; Björneholm, Olle; Huttula, Marko; Alatalo, Matti; Patanen, Minna; et al. (ROYAL SOC CHEMISTRY, 2025)
Hydrogen migration is a ubiquitous phenomenon upon dissociation of organic molecules. Here we investigate the formation of a H3O+ fragment after core-level photoionization and Auger decay in aminobenzoic acid molecules - a process- that requires the migration of at least two hydrogen atoms. Using photoelectron-photoion coincidence spectroscopy, the formation of a H3O+ fragment is observed to be more probable in ortho-aminobenzoic acid than in meta- and para-aminobenzoic acid. Energy-resolved Auger electron-photoion coincidences are measured for the ortho-isomer to investigate the internal energy dependence of the fragmentation channels, most notably of those producing H3O+. The corresponding fragmentation channels and their mechanisms are investigated by exploring the potential energy surface with ab initio quantum chemistry methods and molecular dynamics simulations. Excited-state modeling of dicationic ortho-aminobenzoic acid is used to interpret features in the Auger spectra and identify the electronic states contributing to the signals in the Auger electron photoion coincidence map. We show that populating low-energy excited states of the dication is sufficient to trigger hydrogen migration and produce H3O+ efficiently.